Nurturing care during COVID-19: a rapid review of early evidence - Bernadette Daelmans; Tarun Dua; Vanessa Cavallera; Kristy Hackett; Kerrie Proulx; Rachel Lenzi-Weisbecker; Rachel Hatch; Carina Omoeva (BMJ Open)
Objectives The COVID-19 pandemic has brought significant changes to family life, society and essential health and other services. A rapid review of evidence was conducted to examine emerging evidence on the effects of the pandemic on three components of nurturing care, including responsive caregiving, early learning, and safety and security.Design Two academic databases, organisational websites and reference lists were searched for original studies published between 1 January and 25 October 2020. A single reviewer completed the study selection and data extraction with verification by a second reviewer.Interventions We included studies with a complete methodology and reporting on quantitative or qualitative evidence related to nurturing care during the pandemic.Primary and secondary outcome measures Studies reporting on outcomes related to responsive caregiving, early learning, and safety and security were included.Results The search yielded 4410 citations in total, and 112 studies from over 30 countries met our eligibility criteria. The early evidence base is weighted towards studies in high-income countries, studies related to caregiver mental health and those using quantitative survey designs. Studies reveal issues of concern related to increases in parent and caregiver stress and mental health difficulties during the pandemic, which was linked to harsher and less warm or responsive parenting in some studies. A relatively large number of studies examined child safety and security and indicate a reduction in maltreatment referrals. Lastly, studies suggest that fathers’ engagement in caregiving increased during the early phase of the pandemic, children’s outdoor play and physical activity decreased (while screen time increased), and emergency room visits for child injuries decreased.Conclusion The results highlight key evidence gaps (ie, breastfeeding support and opportunities for early learning) and suggest the need for increased support and evidence-based interventions to ensure young children and other caregivers are supported and protected during the pandemic.